Influence of the design of a mist chamber for the deposition of nanometric thin liquid films – proof-of-concept - Hidalgo, Silvia (2020)
Different designs of mist chambers, intended for the generation of a fine aerosol, were evaluated in terms of its application to deposit a thin liquid film homogeneously on solid surfaces. The developed approach comprises a spray generator that is adapted to the different chambers studied, which is called hereinafter mist chamber. In particular, the utilization of small volume of liquids for the generation of fine mist was in the focus of interest because of its importance for applications where aerosol concentration and size distribution need to be tailored to specific needs. Four mist chamber proposals were evaluated and subjected to experimentation in order to characterize the performance of each proposal. For the proof of concept of the designed mist chambers, a liquid acrylate-based monomer mixture was deposited on silicon wafers and subsequently polymerized by means of an atmospheric-pressure plasma jet. A thorough surface analysis of the obtained films revealed a thickness in the nanometer range as well as a homogeneous deposition pattern.